Safety and effectiveness of a selective strategy for coronary artery revascularization before transcatheter aortic valve implantation. Issue 2 (2nd May 2012) - Gasparetto, Valeria; Fraccaro, Chiara; Tarantini, Giuseppe; Buja, Paolo; D'Onofrio, Augusto; Yzeiraj, Ermela; Pittarello, Demetrio; Isabella, Giambattista; Gerosa, Gino; Iliceto, Sabino; Napodano, Massimo
<x xml:space="preserve">Abstract</x> Objectives We assessed the safety and effectiveness of a selective percutaneous revascularization strategy before TAVI in a single‐center prospective registry. Background Management of Coronary Artery Disease (CAD) before Transcatheter Aortic Valve Implantation (TAVI) is not yet established. Methods Percutaneous Coronary Intervention (PCI) was scheduled in proximal‐to‐mid coronary segment lesions on major coronary branches. TAVI was performed by percutaneous trans‐femoral, trans‐subclavian or trans‐apical approach, using either the self‐expandable III generation CoreValve (Medtronic, Minneapolis, Minnesota USA) or the Edwards SAPIEN™/SAPIEN XT balloon‐expandable prosthesis (Edwards Lifesciences Irvine, CA). Clinical and echocardiographic follow‐up was collected at 30‐day, 3, 6, 12‐month and yearly thereafter. Results Out of 191 patients who underwent TAVI, 113 (59.2%) had CAD. Mean age was 80.5 ± 6.9 years (57.6% female), logistic EuroSCORE was 21.4% ± 13.4. Twenty‐seven (14.1%) patients had previous percutaneous and 29 (15.2%) surgical revascularization. PCI was performed as scheduled before TAVI in 39 (20.4%) patients, without adverse events. Complete anatomical revascularization was obtained in 38 of 113 CAD patients (33.6%). After TAVI, 30‐day mortality was 4.2%, and was comparable between CAD and no‐CAD patients (P = ns), while 30‐day myocardial infarction incidence was 2.6% and occurred only in the CAD group (4.4%, P = 0.06). Overall mortality at follow‐up (12.9 ± 9.5 months) was 14.8%, without difference between groups (P = 0.88). At follow‐up, five patients underwent coronary revascularization. Conclusions In this study, the incidence of CAD is high in patients referred for TAVI. A selective, clinical based, coronary revascularization before TAVI seemed to be safe, and was associated with an outcome similar to those observed in no‐CAD TAVI patients. © 2012 Wiley Periodicals, Inc.